EFEKTIFITAS PEMBELAJARAN NUMERASI BERBANTUAN MEDIA GENIALLY TERHADAP KEMAMPUAN NUMERASI SISWA KELAS IV SD - Septiyanty, Devinda Dwi; Alyani, Fitri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study discusses numeracy as fundamental competence that underpins students’ ability to reason and solve mathematical problems. Despite its importance, students’ numeracy skills in elementary schools remain relatively low, posing a significant challenge in mathematics instruction. Many learners face difficulties in grasping and applying mathematical operations within real-life contexts, engaging in logical reasoning, and developing critical thinking abilities. Additionally, the lack of engaging instructional approaches often hinders students’ conceptual understanding. This study aims to investigate the influence of a numeracy-oriented learning approach enhanced by Genially digital media on the numeracy skills of fourth-grade elementary students. A quantitative method was adopted, employing a quasi-experimental design with a post-test only nonequivalent control group. The experimental group was taught using interactive media via Genially, while the control group received conventional instruction. Data were gathered using a validated and reliable numeracy assessment. The findings revealed that the numeracy-based approach significantly improved student learning outcomes. There was a notable difference between the two groups, with the experimental group achieving higher scores. Statistical analysis showed a Sig. (2-tailed) value of 0.000 and a Cohen’s d effect size of 1.64, indicating a very strong effect. These results suggest that the use of Genially media not only enhances student engagement but also supports a deeper understanding of mathematical concepts through its interactive and visual features. This research highlights the importance of integrating digital tools into numeracy instruction to foster analytical and critical thinking while providing meaningful, contextual learning experiences.